Implementasi Program “Keluar Bersama” dalam Inovasi Pelayanan Publik di Kecamatan Danurejan Kota Yogyakarta - Siti Munawaroh; Dyah Mutiarin (Universitas Medan Area, 2019)
This research discuss about innovation “Keluar Bersama” in Danurejan Subdistrict Yogyakarta City. The research was carried out with the aim of finding out the implementation of the